2013
DOI: 10.1007/s10545-012-9573-z
|View full text |Cite
|
Sign up to set email alerts
|

Farber lipogranulomatosis with predominant joint involvement mimicking juvenile idiopathic arthritis

Abstract: The case of a 10-year-old boy with Farber lipogranulomatosis with predominant joint involvement, subacute, laryngeal and tongue granulomas, microcytic anemia, elevated ESR and CRP, is presented. The boy had no signs of CNS and internal organ involvement. The disease manifested at 6 months; at 11 months the boy had widespread granulomatous polyarthritis with contractures, and juvenile idiopathic arthritis (JIA) was suggested. All antirheumatic therapies failed. Immunologic assessment revealed elevated serum int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…In infants, Farber's disease may present as an acute inflammatory condition mimicking JIA . Hand radiographs of a boy described by Kostik et al showed thinning of the diaphysis and osteopenia, and it is likely that skeletal involvement in that boy may have progressed to look like the osteolysis in our patients. Children with the so‐called intermediate or mild forms may lack neurologic involvement but have severe articular and systemic involvement (particularly of the airways) and may have longer survival times.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In infants, Farber's disease may present as an acute inflammatory condition mimicking JIA . Hand radiographs of a boy described by Kostik et al showed thinning of the diaphysis and osteopenia, and it is likely that skeletal involvement in that boy may have progressed to look like the osteolysis in our patients. Children with the so‐called intermediate or mild forms may lack neurologic involvement but have severe articular and systemic involvement (particularly of the airways) and may have longer survival times.…”
Section: Discussionmentioning
confidence: 61%
“…The c.505T>C (p.Trp169Arg) mutation has been observed in 2 patients with “classic” Farber's disease (Levade T: unpublished observations). The c.760A>G (p.Arg254Gly) mutation has been reported at homozygosity in a young patient presenting in the first year of life with a clinical picture mimicking severe juvenile idiopathic arthritis (JIA) . Genotype–phenotype correlations are not easily recognized in Farber's disease, but the protracted clinical course associated with compound heterozygosity for these mutations is surprising and calls for further studies at the cellular and biochemical level.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, patient 01 carries two point mutations. The c.760A > G substitution (p.Arg254Gly) in exon 10 has already been described . The other one, c.1175G > A, p.Cys392Tyr, has not been described so far.…”
Section: Resultsmentioning
confidence: 96%
“…It is suggested, however, that the actual number of cases is being underestimated due to misdiagnosis 20 . Due to the heterogeneity of FD presentation, a high percentage of cases with mild symptoms are initially diagnosed as juvenile idiopathic arthritis (JIA) 21, 22 . The accurate diagnosis of FD is of crucial importance, as the development of enzyme replacement therapy was announced in July 2016 (Enzyvant Sciences Ltd).…”
Section: Introductionmentioning
confidence: 99%